2017
DOI: 10.1002/hyp.11390
|View full text |Cite|
|
Sign up to set email alerts
|

The role of baseflow in dissolved solids delivery to streams in the Upper Colorado River Basin

Abstract: Salinity has a major effect on water users in the Colorado River Basin, estimated to cause almost $300 million per year in economic damages. The Colorado River Basin Salinity Control Program implements and manages projects to reduce salinity loads, investing millions of dollars per year in irrigation upgrades, canal projects, and other mitigation strategies. To inform and improve mitigation efforts, there is a need to better understand sources of salinity to streams and how salinity has changed over time. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…The degraded water quality of Poyang Lake and its catchment rivers has become a serious problem affecting the ecology and environment (S. Wang, ; Wu, Cai, Zhang, & Chen, ). Many researchers have reported that baseflow plays an important role in the delivery of various materials (e.g., dissolved solids and nutrient concentration) to rivers in catchments (Ford et al, ; Rumsey et al, ). Thus, future work for managers and ecologists studying Poyang Lake should consider the contribution of baseflow to the quality of river and lake water, because 44% to 79% of the streamflow is derived from baseflow (Figures and ) through many subsurface flow paths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degraded water quality of Poyang Lake and its catchment rivers has become a serious problem affecting the ecology and environment (S. Wang, ; Wu, Cai, Zhang, & Chen, ). Many researchers have reported that baseflow plays an important role in the delivery of various materials (e.g., dissolved solids and nutrient concentration) to rivers in catchments (Ford et al, ; Rumsey et al, ). Thus, future work for managers and ecologists studying Poyang Lake should consider the contribution of baseflow to the quality of river and lake water, because 44% to 79% of the streamflow is derived from baseflow (Figures and ) through many subsurface flow paths.…”
Section: Resultsmentioning
confidence: 99%
“…Baseflow refers generally to groundwater discharge flowing into the catchment streamflows, and it is an important component of the groundwater flow system (Ahiablame, Sheshukov, Rahmani, & Moriasi, ; R. Zhang, Chen, Zhang, Soulsby, & Gao, ). It is an important portion of streamflow that generates from shallow, lateral subsurface flow and deep groundwater flow and changes gradually over short‐ and long‐term scales (Nathan & McMahon, ; Rumsey, Miller, Schwarz, Hirsch, & Susong, ). Baseflow sustains river flow between events affected by rainfall–run‐off processes (Miller, Buto, Susong, & Rumsey, ; Shore et al, ; J. Zhang, Zhang, Song, & Cheng, ), which is important for understanding relationships between aquatic habitats and their environment (Ford, King, & Williams, ; Santhi, Allen, Muttiah, Arnold, & Tuppad, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are generally consistent with these studies, as we could relate only 1.4% of basin load to one of our erosion risk index variables (bgm90q.pct). Rumsey et al () also showed that agricultural irrigation areas were associated with increased baseflow loads. This finding is also consistent with our experience in selecting a model strategy that avoided correcting for diversions, which are likely to be moving though short residence time groundwater pathways back into surface waters after being applied for irrigation.…”
Section: Discussionmentioning
confidence: 96%
“…Well-known concentration-streamflow relationships demonstrate that when the bulk of streamflow originates as groundwater discharge, dissolved solids concentrations are typically greatest (Bluth & Kump, 1994;Jennifer C. McIntosh et al, 2017) . Groundwater discharge is often the origin of dissolved solids in watersheds (Rumsey et al, 2017). These conclusions are often based on chemical hydrography separation, which does not provide direct evidence of the depth of groundwater circulation.…”
Section: What Are the Crucial Connections Between Groundwater And Othmentioning
confidence: 99%